2017
DOI: 10.1177/1477153517733504
|View full text |Cite
|
Sign up to set email alerts
|

Spectral optimisation and a novel lighting-design space based on circadian stimulus

Abstract: With the recent advances in photobiology research and light-emitting diode technology, lighting considering circadian effects and the potential health benefits attract much attention. In this study, we demonstrate that the common practice of spectral optimisation of light for high visual efficacy can potentially lead to very inefficient delivery of circadian stimulus, which contributes to the lack of circadian entrainment that is likely to happen in indoor environments with only electric lighting. To optimise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…The first step in obtaining specific spectra from a multi-channel LED luminaire is to calculate the duty cycle for each channel from given visual metrics. Classically, gradient based 90 , heuristic optimization 91 or analytical methods 92 can be used for this purpose. Due to the high number of LED channels in our setup, gradient-based procedures often stuck in local minima.…”
Section: Methodsmentioning
confidence: 99%
“…The first step in obtaining specific spectra from a multi-channel LED luminaire is to calculate the duty cycle for each channel from given visual metrics. Classically, gradient based 90 , heuristic optimization 91 or analytical methods 92 can be used for this purpose. Due to the high number of LED channels in our setup, gradient-based procedures often stuck in local minima.…”
Section: Methodsmentioning
confidence: 99%
“…However, the fundamental trends of the circadian efficacy variation with the luminous efficacy for both circadian models implemented show a notable deviation from each other. In a separate paper [51], Qi Dai et. al. demonstrated that the typical approach of optimizing light by prioritizing high visual quality may lead to ineffective circadian entrainment due to inefficient delivery of circadian activation content in light.…”
Section: Introductionmentioning
confidence: 96%
“…By adjusting the relative luminous flux contributions among the four components, different mixed spectra can be constructed, and the corresponding coordinates can fully cover the gamut shown by the coloured shaded area in Figure 4(a). 4
Figure 4(a) Chromaticity coordinates and (b) spectra of the R/G/B/WW colour components. R/G/B/WW: red/green/blue/warm white (available in colour in online version).
…”
Section: Spectral Optimisation Of the Rgbww Led Synthesized White mentioning
confidence: 99%